Dephasing and dissipation in a source-drain model of light-harvesting systems - Xiong, Shi-Jie (2014)
The energy transport process in natural-light-harvesting systems is investigated by solving the time-dependent Schrödinger equation for a source–network–drain model incorporating the effects of dephasing and dissipation, owing to coupling with the environment. In this model, the network consists of electronically coupled chromophores, which can host energy excitations (excitons) and are connected to source channels, from which the excitons are generated, thereby simulating exciton creation from sunlight. After passing through the network, excitons are captured by the reaction centers and converted into chemical energy. In addition, excitons can reradiate in green plants as photoluminescent light or be destroyed by nonphotochemical quenching (NPQ). These annihilation processes are described in the model by outgoing channels, which allow the excitons to spread to infinity. Besides the photoluminescent reflection, the NPQ processes are the main outgoing channels accompanied by energy dissipation and dephasing. From the simulation of wave-packet dynamics in a one-dimensional chain, it is found that, without dephasing, the motion remains superdiffusive or ballistic, despite the strong energy dissipation. At an increased dephasing rate, the wave-packet motion is found to switch from superdiffusive to diffusive in nature. When a steady energy flow is injected into a site of a linear chain, exciton dissipation along the chain, owing to photoluminescence and NPQ processes, is examined by using a model with coherent and incoherent outgoing channels. It is found that channel coherence leads to suppression of dissipation and multiexciton super-radiance. With this method, the effects of NPQ and dephasing on energy transfer in the Fenna–Matthews–Olson complex are investigated. The NPQ process and the photochemical reflection are found to significantly reduce the energy-transfer efficiency in the complex, whereas the dephasing process slightly enhances the efficiency. The calculated absorption spectrum reproduces the main features of the measured counterpart. As a comparison, the exciton dynamics are also studied in a linear chain of pigments and in a multiple-ring system of light-harvesting complexes II (LH2) from purple bacteria by using the Davydov D1 ansatz. It is found that the exciton transport shows superdiffusion characteristics in both the chain and the LH2 rings.